Mechanical Properties of Interfaces between Mg and SiC: An Ab Initio Study - Yao, Zhipeng; Nasiri, Samaneh; Yang, Mingjun; Zaiser, Michael (Metals, 2024)
Covalently bonded particles may exhibit extremely high strength, but their performance in the reinforcement of metal alloys crucially depends on the properties of their interfaces with the embedding matrix. Here, density functional theory is used for investigating a range of interface configurations between magnesium and silicon carbide in view of their mechanical properties. Interfaces are analyzed not only in terms of interface energy/work of separation but also in terms of the interfacial shear stresses required to induce interface-parallel displacements. These properties are studied for bilayer systems with different orientations of the Mg and SiC layers and for different terminations of the SiC layer (Si or C atoms located at the interface). The results are discussed in terms of their implication for mechanical behavior of SiC reinforced Mg alloys.
Created from Fastlane, Scopus look-up
Keywords: ab initio simulation; interface properties; magnesium; particle-reinforced composites; silicon carbide